Broadband CP corner-truncated microstrip antenna with irregularly hexagonal AMC for 2.45 GHz applications - Purichaya Wichaidit; Sitthichai Dentri; Pisit Janpangngern; Titipong Lertwiriyaprapa; Monai Krairiksh; Chuwong Phongcharoenpanich (Alexandria Engineering Journal, 2024)
This research proposes a compact broadband circularly polarized (CP) corner-truncated microstrip antenna with irregularly hexagonal artificial magnetic conductor (AMC) for 2.45 GHz WLAN applications. The corners of the radiating patch are diagonally truncated to realize circular polarization and improve axial ratio. A 55 irregularly hexagonal AMC array is employed to enhance the axial ratio bandwidth (ARBW) and antenna gain. In addition, a tri-section meandering feedline is used to realize impedance matching and improve the impedance bandwidth (IBW). The AMC array is used to manipulate electromagnetic waves by suppressing surface currents and back lobe, resulting in reduced back radiation and enhanced front-to-back ratio. The simulated IBW and ARBW are 50.9% (1.86 – 3.13 GHz) and 19.3% (2.24 – 2.72 GHz) respectively, with a maximum gain of 8.9 dBic at 2.45 GHz. The measured IBW and ARBW are 42.42% (1.95 – 3.0 GHz) and 29.4% (2.03 – 2.73 GHz), with a maximum gain of 8.6 dBic. The simulated half power beamwidth (HPBW) of the proposed antenna scheme in the xz plane at 2.24 GHz, 2.45 GHz, and 2.72 GHz are 67°, 62°, and 51°, respectively. The corresponding HPBW in the yz plane are 60°, 55°, and 62°. The simulated AR beamwidth in the xz plane at 2.24 GHz, 2.45 GHz, and 2.72 GHz are 177°, 164°, and 88°, respectively. The corresponding AR beamwidth in the yz plane are 148°, 106°, and 124°. The simulated cross polarized (XP) levels at 2.45 GHz are below -19.35 dB for both planes. The measured HPBW in the xz plane at 2.24 GHz, 2.45 GHz, and 2.72 GHz are 69°, 64°, and 50°, respectively. The corresponding HPBW in the yz plane are 65°, 54°, and 37°. The measured AR beamwidth in the xz plane at 2.24 GHz, 2.45 GHz, and 2.72 GHz are 161°, 200°, and 104°, respectively. The corresponding AR beamwidth in the yz plane are 162°, 85°, and 90°. The measured XP levels at 2.45 GHz are below -15.62 dB for both planes. The radiation pattern is unidirectional. Essentially, the proposed broadband CP antenna scheme is suitable for the WLAN frequency band and other 2.45 GHz wireless communication technologies. The novelty of this research lies in the use of the tri-section meandering feedline and the irregularly hexagonal AMC array to enhance IBW and ARBW.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Microwave Engineering and Waveguides